A Beginner’s Guide to Begonias: Seed Propagation - Julian Ginori; Heqiang Huo; Zhanao Deng; Sandra Wilson (EDIS)
This new 4-page publication of the UF/IFAS Environmental Horticulture Department is written for Florida nursery operators, landscape professionals, and individuals interested in propagating their own begonias. This guide goes into detail on how to multiply begonias via pollination/fertilization. Written by Julian Ginori, Heqiang Huo, Zhanao Deng, and Sandra Wilson. https://edis.ifas.ufl.edu/ep619